Reestructuración técnico administrativa de la empresa Camisetas Duna S.A.S. (2019)
In this grade work, an administrative technical restructuring was raised and carried out for the company Camisetas DUNA S.A.S., with the aim of increasing its productivity, focusing on internal and external processes that allow a higher performance production and sales.